Исследование содержания белков-маркеров апоптоза в пульпе временных и постоянных зубов при воспалении (LLC "Endo Press", 2020)
In the present job the maintenance annexin V, caspase-9 and the tumour necrosis factor-α in gomogenates pulps time and second teeth in norm has been investigated and at an inflammation. Results have shown that against an inflammation in a pulp of a deciduous teeth the maintenance annexin V, caspase-9 and the tumour necrosis factor-α increases, and in a pulp of a constant teeth there is an insignificant decrease in quantity annexin V, caspase-9, and the tumour necrosis factor-α in comparison with untouched a pulp is not revealed.